2005
DOI: 10.1186/1477-7525-3-45
|View full text |Cite
|
Sign up to set email alerts
|

Women's quality of life is decreased by acute cystitis and antibiotic adverse effects associated with treatment

Abstract: BackgroundAlthough acute cystitis is a common infection in women, the impact of this infection and its treatment on women's quality of life (QOL) has not been previously described.Objectives: To evaluate QOL in women treated for acute cystitis, and describe the relationship between QOL, clinical outcome and adverse events of each of the interventions used in the study.MethodsDesign. Randomized, open-label, multicenter, treatment study.Setting. Two family medicine outpatient clinics in Iowa.Patients. One-hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 17 publications
3
25
0
Order By: Relevance
“…Ernst et al 220 used the Quality of Wellbeing (QWB) to estimate the QoL among 146 American women who were diagnosed with acute cystitis, and the effect of treatment upon QoL. Those with type 2 diabetes were excluded from the study.…”
Section: Ellis and Vermamentioning
confidence: 99%
“…Ernst et al 220 used the Quality of Wellbeing (QWB) to estimate the QoL among 146 American women who were diagnosed with acute cystitis, and the effect of treatment upon QoL. Those with type 2 diabetes were excluded from the study.…”
Section: Ellis and Vermamentioning
confidence: 99%
“…The underlying mechanism for the association between ADEs and QOL is not fully understood yet. Although, an increase in the experience of ADEs may be associated with a decrease in QOL [ 11 , 12 ], it has also been shown that baseline QOL scores were lower for patients who report an ADE at follow-up than for patients who do not report an ADE at follow-up [ 34 ]. This finding may imply that patients with a low QOL have a higher risk of experiencing ADEs [ 35 ], or that patients with negative health perceptions or certain personality traits are more disposed to experiencing and/or reporting ADEs [ 13 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we used proxies from diabetic foot infection, dermatologic disease, and other infections to estimate utility values 3840. Utilities included in the current model were MRSA infection (0.44),40 treatment success (1, assumption), treatment failure (0.93),39 and drug discontinuation due to an adverse event (0.93) 38. If a patient suffered from multiple health events at the same time, the corresponding utility values were calculated using the multiplicative method.…”
Section: Methodsmentioning
confidence: 99%